Developing Project-Based Electronic Student Worksheet on Number Processing Application Materials - Indah Kristiwi Wahyuningtyas; Agung Listiadi (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2021)
This study aims to develop a project-based electronic student worksheet on the number processing application course for tenth grade and investigate find out teacher's and student's responses to the product. This research and development study using Thiagarajan, Semmel, & Semmel 4D development methods, consisting of define, design, and development stages. Meanwhile, while the dissemination stage has not been carried out because of the limitations. This development aims to produce a project-based e-student worksheet, to analyze the project's development stages, and to analyze the feasibility of the project. This research material has been evaluated and validated by one of the teachers from Ketintang Vocational High School Surabaya and accounting education lecturer, education technology lecturer, and linguistic lecturer from Universitas Negeri Surabaya. The research subjects were tenth-grade accounting students in Ketintang Vocational High School, Surabaya. The data were analyzed using quantitative and qualitative analysis techniques. Meanwhile, the instrument involved in this study were open-questionnaire and close-questionnaire.